Stress concentration mitigation in clamped steel plates - Kalita, Kanak (International Journal of Scientific World, 2014)
Steel is used widely in the construction of roads, railways, other infrastructure, appliances, and buildings. Most large modern structures, such as stadiums, skyscrapers, bridges, airports, are supported by a steel skeleton. Steel plates with internal cutouts are widely used in structural members. These cutouts are made into plates to meet various functional and structural requirements. However these cutouts create stress concentration and eventually reduce the mechanical strength of the structure. The present study aims at reducing this stress concentration around the central hole by introduction of a proposed scheme of auxiliary holes. Reduction in stress concentration with symmetric and asymmetric auxiliary holes is studied. Findings of the study are made available here in both numerical data and graphical form. Keywords: Auxiliary Hole, Cutout Plate, Finite Element Method, Stress Mitigation, Stress Analysis.